Judges in politics or politicians in courts? Reflections around the judicialization of politics from cases of Latin America - Ramos Rollón, Marisa (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
In this article, the phenomenon of the judicialization of politics is analyzed, providing a review of the concept and its expressions that could facilitate its empirical contrast. The nature of the concept, its different meanings and the possible confusion generated by the association of the phenomenon with the substantive aspect of the judicial process rather than the organic one, that is, the political as matter, are reviewed. To advance the possibilities of empirical observation, a typology of expressions of judicialization of politics is proposed, which is subsequently contrasted with paradigmatic cases in Latin America.